Implementing Multicultural Education in Indonesian State Islamic Universities: Case Studies of UIN Sunan Kalijaga and UIN Sulthan Thaha Saifuddin - Sibawaihi; Mohd. Arifullah; Moh. Solikul Hadi (Jurnal Pendidikan Islam, 2025)
Purpose – The study aims to investigate how multicultural education has been implemented in the state Islamic universities in Indonesia and what strategies have been applied by the universities in promoting and imparting multicultural education to students. Two representing universities have been selected: UIN Sunan Kalijaga Yogyakarta and UIN Sulthan Thaha Saifuddin Jambi. Design/methods/approach – This is qualitative study using direct data collection. Data were collected through interview, document analysis, and observation. Data were analyzed through descriptive analysis and critical analysis. Descriptive analysis has provided detailed information about the implementation of multiculturalism. Critical analysis has allowed researchers to examine and criticize various multicultural education tasks on both campuses. Findings – The authors found that in implementing multicultural education, both universities have built an equity pedagogy by bringing multiculturalism into the learning process, have integrated multicultural content into learning, have inculcated multiculturalism insight in the process of constructing knowledge, and have made efforts to reduce prejudice and empower school culture. The strategies adopted to promote and impart multicultural education to students are adapting the curriculum, promoting equality through campus activities, optimizing the strategic role of lecturers in instilling multiculturalism insights directly into students, forming study centers with multiculturalism insight, and maintaining the uniqueness of each university in fighting for equality. Research implications – Since the study covers state Islamic universities in Indonesia, it could contribute to the effort to promote multiculturalism in all the higher education institutions under the Ministry of Religious Affairs. Based on the idea that campus residents are dynamic, critical, creative, multifaceted, and inventive creatures, it is important to create a campus environment that prioritizes an atmosphere of justice, equality, comfort, and security for all campus social entities.